2016
DOI: 10.1038/srep23180
|View full text |Cite
|
Sign up to set email alerts
|

A cationic tetrapyrrole inhibits toxic activities of the cellular prion protein

Abstract: Prion diseases are rare neurodegenerative conditions associated with the conformational conversion of the cellular prion protein (PrPC) into PrPSc, a self-replicating isoform (prion) that accumulates in the central nervous system of affected individuals. The structure of PrPSc is poorly defined, and likely to be heterogeneous, as suggested by the existence of different prion strains. The latter represents a relevant problem for therapy in prion diseases, as some potent anti-prion compounds have shown strain-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 63 publications
3
40
0
Order By: Relevance
“…1, C and D). The effect of TMPyP in the DBCA was recently reported by Massignan and colleagues (35). Given this correlation between the inhibitory activity of compounds in ScN2a cells and in the DBCA, we decided to use the DBCA as the read-out in a high-throughput screen to see if we could discover previously unknown molecules that might also have anti-prion activity.…”
Section: Resultsmentioning
confidence: 99%
“…1, C and D). The effect of TMPyP in the DBCA was recently reported by Massignan and colleagues (35). Given this correlation between the inhibitory activity of compounds in ScN2a cells and in the DBCA, we decided to use the DBCA as the read-out in a high-throughput screen to see if we could discover previously unknown molecules that might also have anti-prion activity.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, cells exposed to zeocin alone showed a strong decrease in viability (<70 %, not shown). Conversely, co‐treatment with the porphyrin Fe III ‐TMPyP, previously shown to inhibit the activity of ΔCR PrP in the DBCA, abrogated the effect (not shown). Among the different compounds, we identified eight molecules ( 34 , 38 , 39, 43 , 46, 50 , 53 and 54 ) capable of rescuing at least 20 % of antibiotic‐induced cell death (Figure ).…”
Section: Figurementioning
confidence: 80%
“…We have previously described the DBCA, a cellular assay based on the intrinsic cytotoxic effects of PrP molecules carrying mutations in the central region of the protein . Multiple previous studies indicated that this assay is a useful tool to study PrP‐mediated neurotoxic pathways, as well as to identify and characterize novel anti‐prion compounds . Here, we used the DBCA to screen a representative diverse set of small molecules from an original collection of chemicals developed at EDASA Scientific.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Here we have examined the effects on α‐synuclein of a tetrapyrrole that was initially discovered in a screen for inhibitors of prion disease, iron(III) meso‐ tetra ( N ‐methyl‐4‐pyridyl‐prophine) (Figure ), denoted hereafter as Fe‐TMPyP. Fe‐TMPyP, which was first proposed to act by stabilizing the natively structured C‐terminal domain of PrP, via specific binding with a stoichiometry of 1, is effective at inhibiting a broad range of prion strains, unlike other anti‐prion compounds . However, it was later found to have high affinity also for the C‐terminal domain when unfolded, with its binding preventing the formation of stable misfolded aggregates .…”
Section: Introductionmentioning
confidence: 99%